Arang aktif sekam padi sebagai bahan pengisi kompon sol karet - Arum Yuniari; Sri Brataningsih Puji Lestari (Majalah Kulit, Karet, dan Plastik, 2003)
The aim of this research was to investigate the properties of activated carbon from rice husk filler in their application on vulcanized rubber soles, and to determine its suitability for rubber compound, the  properties of activated carbon from rice husk filler in their application on vulcanized rubber soles, and to determine its suitability for rubber compound, the properties of activated carbon made from rice husk was investigated by comparing with cabon black N 330. Activated carbon made from rice husk was made by carbonization process at temperature of 4500C for 1 hour and activation process with NaCL  4%  for 24 hours followed by pyrolysis at temperature 5000C for 1 hour. Filler was milled and sieved by 400 mesh siefter. The research showed that using activated carbon in the amount 20 phr and carbon black N330 40 phr. Fulfill the requirement at SNI : 12-0172-1987 : Canvas shoes sole for general purpose, where as tensile strength 11,24 N/mm2, elongation at break : 699%, tear strength  2,97 N/mm2, hardness : 65,7 shore A, density 1,23 gram/cm2, permanent set 0,10%, abrasion 0,72 mm3/ kgm and flexing at 250 kcs no crack.   Keywords : rice husk, rubber, filler